Evaluation of Mechanical Behavior of Nuclear Component Materials Using Automated Ball Indentation Approach - Khandelwal, Harshit Kumar (My University, 2011)
Automatic ball indentation (ABI) is a non-destructive methodology to determine the mechanical properties of materials. Moreover, it is a promising method for in-situ assessment of mechanical properties. For in-situ application it is almost non-destructive since almost no material is removed from the test surface. Hence, it could prove valuable in the evaluation of mechanical properties of different materials of nuclear applications at different environmental conditions. In the present work, mechanical behavior of nuclear component materials (bimetallic weld joint, similar weld joint, reactor pressure vessel material, and pressure tube material) at different conditions was studied using Automated Ball Indentation approach. In this respect, material properties (yield strength, ultimate tensile strength, strength coefficient, and strain hardening exponent) of nuclear component materials were studied using ABI approach. Characterization of bimetallic weld joint and similar weld joint shows how mechanical properties vary from zone to zone, and from point to point in each zone of weld joint used in nuclear application using Automated Ball Indentation approach. The present work is also an attempt to characterize the mechanical behavior degradation of reactor pressure vessel materials during their operation in typical radiation environmental conditions (radiations of neutrons, alpha, beta, gamma rays and fission products) existing inside the nuclear reactor. The present work is also an attempt to show the modified fabricating procedure of zirconium alloy (Zr-2.5-Nb) pressure tube of a pressurized heavy water reactor. For this purpose, mechanical behavior examination of Zr-2.5- Nb alloy at different environmental condition was performed with the help of ABI methodology. Finally, analytical investigation of ABI approach was performed. For this purpose, 2D axis symmetric finite element model was prepared and simulated using ANSYS software.
Master of Engineering, MED
Keywords: ABI Testing; Nuclear Reaction; SS-304; SA-508; Zr-2.5 Nb; Pressure vessel; Pressure Tube Material